Modificações no periodonto de ratos diabéticos após a movimentação ortodôntica - Vila Real, Luis Alberto Sabino; Ramos, Adilson Luiz [UNESP]; Zanoni, Jacqueline Nelisis (FapUNIFESP (SciELO), 2009)
Aim: The aim of this study was to evaluate the periodontal ligament changes after induced dental movement of the upper incisor in diabetic rats. Methods: Twenty Wistar rats (Rattus norvegicus) with 105 days of age were used. The rats were divided in four groups: C - normoglicemic animals not submitted to dental movement; CAO - normoglicemic animals submitted to dental movement; D - diabetic animals not submitted the dental movement; DAO - diabetic animals submitted to dental movement. The animals had remained with dental movement devices during 5 days. The number of sanguine vessels and the thickness of the periodontal ligament were evaluated at cervical, medium and apical histological cut regions. Results and Conclusion: At tension side, the dental movement in the animals of group CAO resulted in a thicker periodontal ligament (17.64% apical, 39.28% medium, 51.35% cervical) when compared to C group (p < 0.05 for medium and cervical area). Group DAO exhibited an increase of periodontal ligament thickness of 50.55% (apical), 48.14% (average) and 50% (cervical) when compared to group D (p < 0.05). The periodontal ligament sanguine vessels number did not differed significantly for all groups (p < 0.05). At tension side, bone reabsorption lacunae were observed in CAO, D and DAO groups. The pressure side was not examined in this study phase.
Periodontal ligament changes after induced dental movement in diabetic rats
Keywords: Dental movement; Diabetes mellitus; Periodontal ligament